Cotidiano e práticas curriculares de escolas cívico-militares em Minas Gerais e Santa Catarina - Maximiano, Eric Gabriel de Aguiar (Universidade Federal de São Carlos, 2026)
This master's research analyzes the curriculum and daily practices of state civic-military schools, investigating the tensions between militarized management and the principles of democratic education. Grounded in Critical Theory (Adorno, Horkheimer), Critical Pedagogy (Giroux), and Paulo Freire, the study questions whether the model promotes emancipation or authoritarian conformity. The qualitative methodology involved documentary analysis and semi-structured interviews with managers, teachers, military monitors, and students from two schools: one in Minas Gerais (partnership with the Fire Department) and another in Santa Catarina (Military Police/Reserve). The results indicate that the success attributed to the model does not stem exclusively from military discipline but masks a selective input of human and financial resources, operating as a political "showcase" that hides the precariousness of the regular school system. It was observed that the military presence is resignified by the school community: in Minas Gerais, it assumes a character of assistance and "care"; in Santa Catarina, of security and marketing. It is concluded that the model promotes the naturalization of hierarchy and the fragmentation of teaching work, sustaining itself on affective identification with authority and the "parental illusion" of order, to the detriment of students' critical formation.
Daily life and curricular practices of civic-military schools in Minas Gerais and Santa Catarina
Keywords: Escolas cívico-militares; Teoria Crítica; Gestão Escolar; Currículo Oculto; Política Educacional; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade